The ESCAPS study: a feasibility randomized controlled trial of early electrical stimulation to the wrist extensors and flexors to prevent post-stroke complications of pain and contractures in the paretic arm. (December 2019) - Fletcher-Smith, Joanna C; Walker, Dawn-Marie; Allatt, Kate; Sprigg, Nikola; James, Marilyn; Ratib, Sonia; Boadu, Janet; Richardson, Carla; Pandyan, Anand D
Objective: To establish feasibility of initiating electrical stimulation treatment of wrist extensors and flexors in patients early after stroke to prevent muscle contractures and pain. Design: Feasibility randomized controlled trial with economic evaluation. Setting: A specialist stroke unit in Nottinghamshire. Subjects: A total of 40 patients recruited within 72 hours post-stroke with arm hemiparesis. Interventions: Participants were randomized to receive usual care or usual care and electrical stimulation to wrist flexors and extensors for 30 minutes, twice a day, five days a week for three months. Initial treatment was delivered by an occupational therapist or physiotherapist who trained participants to self-manage subsequent treatments. Measures: Measures of feasibility included recruitment and attrition rates, completion of treatment, and successful data collection. Outcome data on wrist range of motion, pain, arm function, independence, quality of life, and resource use were measured at 3-, 6-, and 12-months post-randomization. Results: A total of 40 participants (of 215 potentially eligible) were recruited in 15 months (20 men; mean age: 72 (SD: 13.0)). Half the participants lacked mental capacity and were recruited by consultee consent. Attrition at three-month follow-up was 12.5% (death ( n = 2), end-of-life care ( n = 2), and unable to contact ( n = 1)). Compliance varied (mean: 65 (SD: 53)) and ranged from 10 to 166 treatments per patient (target dosage was 120). Data for a valid economic analysis can be adequately collected. Conclusion: Early initiation of electrical stimulation was acceptable and feasible. Data collection methods used were feasible and acceptable to participants. A large definitive study is needed to determine if electrical stimulation is efficacious and cost effective.